GEOECONOMIC FRAGMENTATION: LIKELIHOOD OF GLOBAL FINANCIAL RECESSION AND ANALYSIS OF BANKING RISKS IN UKRAINE - LIKHONOSOVA, Ganna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article was prepared as part of the scientific study "Mechanism of levelling socio-economic rejection of the population of Ukraine in conditions of economic turbulence." The article updates the problem of independent organization of business entities in conditions of economic turbulence, a changing external environment of functioning and an unpredictable information space, which occurs in parallel with the development of processes of socialization of the economy to meet the material, cultural, and spiritual needs of society. It is assumed that the main characteristic of the self-organization of the enterprise is the ability for continuous self-improvement with a continuous increase in production efficiency. Turbulence in the socio-economic system is caused not only by economic, but also non-economic reasons, in particular, demographic, ecological, technological factors, military conflicts. The fact of being in a state of turbulence due to the dynamics of indicators of population migration and public debt is characterized. The author’s vision of methodological configurations and models of innovative interaction of business entities in accordance with the conditions of global challenges is presented. The development of the "Washington Consensus" agreement, which provided for the liberalization of trade, direct foreign investment and privatization, and its impact on the currency positions and export potential of the world’s leading economies is characterized. It is emphasized that the basis of multivariability is the passage of the system through bifurcation points, exits of the system from the state of homeostasis, transition of the system into an unbalanced state. It is at the point of bifurcation that the search for a new path takes place, the implementation of one of many possible options. It is predicted that the realities will move Ukraine to the point of bifurcation and a real exit from the systemic crisis is possible thanks to a qualitative change in its leading idea - representation on the financial market, construction of the architecture of new target orientations, which form a new vector direction of development in search of positive synergistic effects. Ensuring this is possible on the basis of the use of a synergistic paradigm of development, volitional vector definition of the goal, the methodology of information-synergistic meaningful analysis and management technologies based on forecasting, scenario modelling, strategic planning, which are a mechanism of state-building management and the construction of a future socio-economic foresight for Ukraine.